"He was like, my ride or die": Sexual and Gender Minority Emerging Adults' Perspectives on Living With Pets During the Transition to Adulthood. Issue 4 (August 2022) - McDonald, Shelby E.; Matijczak, Angela; Nicotera, Nicole; Applebaum, Jennifer W.; Kremer, Liza; Natoli, Grace; O'Ryan, Ryan; Booth, Laura J.; Murphy, Jennifer L.; Tomlinson, Camie A.; Kattari, Shanna K.
This qualitative study explores the benefits and risks associated with living with companion animals during the transition to adulthood among 117 sexual and gender minority (SGM) emerging adults living in the U.S. Interviews were transcribed and analyzed using template analysis. Thematic analysis identified several risks (caregiver burden, pets as barriers to relationships, animal-related psychological stress) and benefits (pets as a buffer to stress, pets as social capital, pets as a coping mechanism for mental health, and pets as identity and purpose) associated with living with pets. Our results suggest that pets may influence SGM emerging adult identity development and related wellbeing by facilitating feelings of belongingness, positive self-regard, and purpose; promoting social interactions; and providing emotional support and comfort to cope with stress. However, pets, and their associated care, were also a source of caregiving burden and psychological stress. We discuss practice and policy implications and directions for future research.